RETRACTED ARTICLE: Microbial and Physicochemical Profile of Fresh Water Fish Pond in Bahawalpur Region, Punjab Pakistan - Hanif, Muhammad Saleem; Jabbar, Muhammad (PSM Microbiology, 2021)
A microbial and physicochemical study of six freshwater fish ponds was carried out. The physicochemical parameters results showed that Total Dissolved Solids are significant in the production ponds (693.75±9.00 to 759.75±1.88), higher conductivity in the growth ponds, (1220.50±2.91 to 1220.50±10.52) and all the ponds showed non-significant hardness and chloride values (266.25±3.14 to 321.25±22.94), highly significant turbidity (1.22±0.09 to 5.90±1.17) among all the ponds. In the bacteriological examination, 15 different bacterial species were identified, Aeromonas hydrophila, Escherichia coli, Salmonella enterica, Vibrio sp. Pseudomonas aeruginosa, Proteus mirabilis, Enterobacter aerogenes, Klebsiella pneunomiae, Serratia liquefaciens, Streptococcus sp., Flavobacterium columnare, Listeria monocytogenes, Pleisomonas shigelloides, and Citrobacter freundii. The intestine of these fishes was found rich with these pathogens but the muscles were free from all types of microflora. The study revealed that production ponds which have consumable fish are contaminated with pathogenic bacteria and may be the source of potential pathogens to human via fish handler, thus there is need to address this issue of public health concern.